Using information communication technology to identify deficits in rural health care: a mixed-methods evaluation from Guatemala - Wahedi, Katharina; Flores, Walter; Beiersmann, Claudia; Bozorgmehr, Kayvan; Jahn, Albrecht (Global health action, 2018)
Background: In August 2014, the Centre for the Studies of Equity and Governance in Health Systems (CEGSS) in Guatemala launched an online platform, which facilitates complaints about health services via text messages. The aim is to collect, systemise and forward such complaints to relevant institutions, and to create a data pool on perceived deficits of health care in rural Guatemala.Objective: To evaluate if the online platform is an accepted, user-friendly and efficient medium to engage citizens in the reporting of health care deficiencies in Guatemala.Methods: The general study design of this research was a mixed-method approach including a quantitative analysis of complaints received and a qualitative exploration of the attitude of community leaders towards the platform.Results: User statistics showed that a total of N = 228 messages were sent to the platform in the period August 2014-March 2015. The majority of complaints (n = 162, 71%) fell under the ‘lack of drugs, equipment or supplies’ category. The community leaders welcomed the platform, describing it as modern and progressive. Despite feedback mechanisms and methods to respond to complaints not yet being fully developed, many users showed a high intrinsic motivation to use the new tool. Others, however, were restrained by fear of personal consequences and distrust of the state’s judicial system. Access to mobile phones, reception, and phone credit or battery life did not pose major obstacles, but the producing and sending of correctly formatted messages was observed to be difficult.Conclusion: The online platform paired with SMS technology appears to be a viable approach to collect citizens’ complaints in health care and connect citizens with relevant institutions. Further studies should be conducted to quantify follow-up activities and the impact on local health care provision.